2017
DOI: 10.1016/j.jpba.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolic profiling of cisplatin nephrotoxicity and nephroprotective effects of Orthosiphon stamineus leaves elucidated by 1 H NMR spectroscopy

Abstract: Orthosiphon stamineus (OS) is a popular medicinal herb used in traditional Chinese medicine as a diuretic agent and for renal system disorders. This study employed H NMR based metabolomics approach to investigate the possible protective activity of OS in cisplatin induced nephrotoxicity owing to its diuretic and antioxidant activities. Aqueous (OSAE) and 50% aqueous ethanolic (OSFE) extracts of OS leaves were orally administered at 400mg/kg BW doses to rats which were then intraperitoneally injected with cispl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…However, increased intensity of signal of two metabolites related to amino acid metabolism, creatine and glycine, separate the cluster of FAIG-Mi, while creatine alone contribute for FAIG-S. Increased urinary glycine was also observed in cisplatin nephrotoxicity rats (Pariyani et al 2017;Ryu et al 2019). It is possible the result from injury in the proximal tubule, given that an increased presence of glycine in urine has been described in animals treated with proximal tubule toxins, or with pathologies affecting the proximal tubule (Zuppi et al 1997).…”
Section: Discussionmentioning
confidence: 96%
“…However, increased intensity of signal of two metabolites related to amino acid metabolism, creatine and glycine, separate the cluster of FAIG-Mi, while creatine alone contribute for FAIG-S. Increased urinary glycine was also observed in cisplatin nephrotoxicity rats (Pariyani et al 2017;Ryu et al 2019). It is possible the result from injury in the proximal tubule, given that an increased presence of glycine in urine has been described in animals treated with proximal tubule toxins, or with pathologies affecting the proximal tubule (Zuppi et al 1997).…”
Section: Discussionmentioning
confidence: 96%
“…The HPLC quantification of two major marker compounds of OS, namely rosmarinic acid and sinensetin, in OS aqueous extract was carried out, in accordance with the methods described in our published report on OS [21]. …”
Section: Methodsmentioning
confidence: 99%
“…Published literature showed that the main compounds in OS are flavonoids, terpenes, and caffeic acid derivatives (Sumaryono et al, 1991;Tezuka et al, 2000). At present, researches on OS for the treatment of kidney diseases such as nephritis, kidney infection and cisplatin nephrotoxicity have been widely carried out (Hiromitsu et al, 2003;Pariyani et al, 2017;Sarshar et al, 2017), especially in the treatment of kidney stones. For instance, the 50% methanol extract of OS inhibits the calcium oxalate crystal growth (Dharmaraj et al, 2006) and aqueous extract of OS has protective effect in a calcium oxalate stone forming (Akanae et al, 2010).…”
Section: Introductionmentioning
confidence: 99%